Types of security strategies of small states: compilation and opposition - Galstyan, Narek (YSU Journal of International Affairs, 2021)
The article analyses and groups some security strategies of small states towards the great powers according to the principle of their final result - the impact on the security and independence of the state. It is hypothesized that all strategies of small states can be grouped into four groups: compilation, opposition, self-exclusion, and application. In particular, a list of strategies and the main characteristics of strategies are given, which, according to their final results, can be attributed to the first two groups. The main conditions for the realization of these groups of strategies are also identified. In the conclusion, the main differences and commonalities of these two groups of strategies are noted.
Keywords: small state; great power; foreign policy; security; strategy; alliance